Ethernet interface for embedded web server [microfilm] - Noor Azurati Ahmad @ Salleh (Skudai : Universiti Teknologi Malaysia, 2001)
Project Paper (Bachelor of Engineering (Electrical-Computer)) - Universiti Teknologi Malaysia, 2001